The role of product nationality in purchase behavior - Dmitrović, Tanja (Array, 2009)
Abstract: The article examines the impact of product nationality cues on consumer behavior and presents the results of two studies based on large-scale surveys of adult consumers from four countries of the South-East Europe: Croatia, Bosnia and Herzegovina, Serbia, and Montenegro. The results indicate that consumer ethnocentrism affects domestic purchase behavior both directly and indirectly through domestic product quality evaluation. Ethnic affiliation of consumers has a direct effect on both consumer ethnocentrism and on domestic purchase behavior. However, the findings on the role of identification to the nation and openness to other cultures as antecedents to consumer ethnocentrism and/or to domestic product quality evaluation were not consistent across countries and across studies, indicating a need for further research on the influence of affective processing mechanisms in consumption. Theoretical and managerial implications of both studies are discussed, together with some recommendations for public policy regarding the support of "buy domestic" campaigns